Strategi Pembelajaran Kooperatif dapat Meningkatkan Karakter Gotong Royong Anak Sekolah Dasar - Milah Akmaliah; Tita Hasanah; M. Zainal Arifin (Primer Edukasi Journal, 2022)
This thesis aims to determine the improvement of the mutual cooperation character of Warung Saptu Elementary School students through cooperative learning strategies which are thought to be able to improve the mutual cooperation character. The research method used is classroom action research (PTK). This method is carried out in several stages, namely planning, action, observation and reflection. These stages are cycles that occur repeatedly and are carried out with the same steps. The data collection methods used were interviews, questionnaires and observations. The research results show that implementing cooperative learning strategies can improve the character of mutual cooperation. This can be seen from the increase in questionnaire results every cycle. The increase from each cycle, namely in cycle 1, the average student score reached 79% in the moderate category, increased in cycle 2 to 82% in the high category and increased again in cycle 3 to 92% in the very high category.